2020
DOI: 10.1098/rsta.2020.0031
|View full text |Cite
|
Sign up to set email alerts
|

Direct drive with the argon fluoride laser as a path to high fusion gain with sub-megajoule laser energy

Abstract: Argon fluoride (ArF) is currently the shortest wavelength laser that can credibly scale to the energy and power required for high gain inertial fusion. ArF's deep ultraviolet light and capability to provide much wider bandwidth than other contemporary inertial confinement fusion (ICF) laser drivers would drastically improve the laser target coupling efficiency and enable substantially higher pressures to drive an implosion. Our radiation hydrodynamics simulations indicate gains greater than 100 are feasible wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The higher frequency laser has a higher critical density and thus propagates further into the plasma, resulting in more laser absorption and a higher density blow-off (Obenschain et al. 2020). Furthermore, the lower wavelength permits higher laser intensities before the onset of parametric instabilities (Montgomery 2016), enabling higher laser powers to be used for equivalent instability growth.…”
Section: High Frequency and Two-colour Implosionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher frequency laser has a higher critical density and thus propagates further into the plasma, resulting in more laser absorption and a higher density blow-off (Obenschain et al. 2020). Furthermore, the lower wavelength permits higher laser intensities before the onset of parametric instabilities (Montgomery 2016), enabling higher laser powers to be used for equivalent instability growth.…”
Section: High Frequency and Two-colour Implosionsmentioning
confidence: 99%
“…Recent simulation work by Obenschain et al. (2020) demonstrated that significant gains can be achieved at low laser energy using wavelength nm ArF laser drivers when applied to shock ignition, leading the authors to highlight the potential role of such lasers for IFE applications. In order to investigate these advantages further the optimisation process performed in Paddock et al .…”
Section: High Frequency and Two-colour Implosionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Part I concluded with a fascinating discussion of the benefits of deploying the Naval Research Laboratory's argon-fluoride (ArF) driver, operating at a wavelength of 193 nm, for direct drive of inertial fusion targets. Their work suggests that a significant saving on drive energy (and capital costs) might be realized using this approach [14].…”
Section: Introductionmentioning
confidence: 99%
“…The first edition of this special issue concludes with Stephen Obenschain et al ’s very interesting article ‘Direct-drive with the Argon Fluoride laser as a path to high-gain with sub-megajoule laser energy’ [13] describing the potential benefits of using still shorter wavelengths (193 nm) that are available with argon-fluoride excimer lasers as the driver to achieve high gains for inertial fusion energy.…”
Section: Introductionmentioning
confidence: 99%